(untitled) (FULafia Journal of Science and Technology, 2019)
Over the years, medicinal plants have been used not only as a source of food but also in the treatment of many diseases in various parts of the world. In Nigeria, Moringa oleifera and Vernonia amygdalina are some of the common plants whose parts have contributed to the increased intake of essential nutrients and healthpromoting phytochemicals. The lime, aqueous and ethanolic extracts of combined Moringa oleifera and Vernonia amygdalina was studies for their toxic effect and thus the LD50 was determined. It was seen that lime extract had the highest weight loss effect and also the highest mortality rate, however the LD50 values for the three extracts of 900mg/kg, showed that the extracts had an acceptable LD50 values and thus its use in trado-medicine is left uncontested.